2018
DOI: 10.1002/dneu.22583
|View full text |Cite
|
Sign up to set email alerts
|

Adult spinal opioid receptor μ1 expression after incision is altered by early life repetitive tactile and noxious procedures in rats

Abstract: Clinical and experimental data suggests that noxious stimulation at critical stages of development results in long‐term changes on nociceptive processing in later life. Here, we use an established, well‐documented rat model of repetitive noxious procedures closely mimicking the clinical situation in the NICU. In order to understand molecular changes underlying the long‐term consequences of repetitive stimulation of the developing nociceptive system the present study aims to analyze the presence of the µ‐opioid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Previous studies by our group using this model did not show mechanical hyposensitivity in later life. 17,23,29 However, several studies have suggested changes in nociception in adulthood after early life maternal separation, 30,31 showing reduction in sensitivity in adult females after neonatal maternal separation. 31 Possibly, the cumulative separation stress and needle pricks led to hyposensitivity as observed here.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies by our group using this model did not show mechanical hyposensitivity in later life. 17,23,29 However, several studies have suggested changes in nociception in adulthood after early life maternal separation, 30,31 showing reduction in sensitivity in adult females after neonatal maternal separation. 31 Possibly, the cumulative separation stress and needle pricks led to hyposensitivity as observed here.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in spinal 5-HT staining intensity may contribute to the sensitized spinal nociceptive network after neonatal procedural pain due to lower levels of descending serotonergic projections and serotonin levels in the dorsal horn. Despite the observed anatomical and biochemical changes in the spinal nociceptive network after procedural neonatal pain, mechanical sensitivity at baseline is unaltered after neonatal procedural pain (de Kort, Joosten, Patijn, Tibboel, & van den Hoogen, 2021b; Knaepen et al, 2013;van den Hoogen et al, 2016;van den Hoogen, van Reij, Patijn, Tibboel, & Joosten, 2018). In line with this, depletion of descending serotonergic projections does not alter mechanical or thermal sensitivity (Minor et al, 1988;Palm et al, 2008;Wei et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Mechanical sensitivity during development and after re-injury in adulthood After weaning at the age of 3 weeks, mechanical sensitivity was tested weekly until adulthood using Plantar application of Von Frey filaments as described previously. 18,21,33 In short, animals were placed individually in Plexiglass chambers on a mesh floor and left to habituate. A range of Von Frey filaments (0.4, 0.6, 1.0, 2.0, 4.0, 6.0, 8.0, 15.0 and 26.0 g) was applied for 5 s onto the midplantar surface of both hind paws, starting with 1.0 g. If no response was observed, the filament with a larger force was applied next.…”
Section: Methodsmentioning
confidence: 99%
“…[14][15][16][17][18][19][20] The changes in pain behaviour have been correlated to underlying changes in spinal and supraspinal anatomy and functionality. 14,17,21,22 Previously, we have shown that neonatal repetitive procedural pain leads to spinal hyperexcitability, expressed as an increased firing of secondary pain transmission neurons. 17 This increase in firing is possibly linked to N-methyl-D-aspartate receptor (NMDA-R)-mediated central sensitization lasting into adulthood.…”
Section: Introductionmentioning
confidence: 99%